DETERMINATION OF ALPRAZOLAM AND FLUOXETINE HCl FROM SPIKED RAT PLASMA USING HPTLC WITH UV DETECTION - Thomas, Asha B.; Naphade, Ashish; Karanjkhele, Snehal S. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The main aim of this study was to develop a rapid, simple and selective validated high-performance thin-layer chromatographic (HPTLC) method with UV detection for the estimation of alprazolam and fluoxetine HCl from spiked rat plasma. Methods: In this method, a mixture of acetonitrile and chloroform (2:4 v/v) was employed as the solvent for extraction of alprazolam and fluoxetine HCl from spiked rat plasma samples with good sample recovery. The separation was achieved on a 20 cm x10 cm TLC plate precoated with silica gel 60F254, the 250μm thickness on aluminium sheets employing a mobile phase consisting of ethyl acetate: toluene: methanol: ammonia (4:3:1:0.1v/v/v/v). The densitometric evaluation was performed at 230 nm. The developed method was validated as per the recommendations of USFDA Guidance for Industry: Bioanalytical Method Validation. Results: The Rf value were observed at 0.48±0.04 and 0.17±0.02 for alprazolam and fluoxetine HCl respectively. The calibration curves were linear in the range of 40-100 ng/μl for both drugs with regression coefficients (r2) of 0.9910 and 0.9932 for alprazolam and fluoxetine HCl respectively. In the intraday and interday precision study, the % CV was less than 15. Results of recovery studies prove the extraction efficiency of the proposed method. Stability data indicated that both alprazolam and fluoxetine HCl were stable in plasma after three freeze-thaw cycles and upon storage at -20 °C for 1 w. Conclusion: In the proposed method, the rapid, single step extraction of drugs from plasma samples coupled with the simple HPTLC-UV chromatographic conditions makes the method cost effective and suitable for analysis of a large number of binary samples of alprazolam and fluoxetine HCl in plasma. Keywords: Alprazolam, Fluoxetine HCl, Bioanalytical method, Liquid-liquid extraction, HPTLC, Spiked rat plasma